PREDIKSI HARGA CABAI RAWIT DI PASAR INDUK MANDALIKA KOTA MATARAM DENGAN METODE ARIMA BOX-JENKINS - Setiawan, Rifani Nur Sindy; Widiyanti, Ni Made Nike Zeamita; kusuma, wirajaya (JURNAL AGRIMANSION, 2025)
Cayenne pepper is an important commodity for the economy of the people in Mataram City. Cayenne pepper is the main complementary seasoning for the people of Mataram City, this is because the typical cuisine of the residents here has a spicy taste. Fluctuations in the price of cayenne pepper are one of the problems that often occur every year. Fluctuations in the price of cayenne pepper will certainly affect the demand and income of cayenne pepper farmers. Based on this, the purpose of this study is to predict the price of cayenne pepper in Mandalika Main Market in 2025 using the ARIMA Box-Jenkins method. Cayenne pepper price data comes from secondary data from January 2020 to December 2024. Based on the results of the analysis conducted with the ARIMA Box-Jenkins method, the best model used to predict the retail price of cayenne pepper at the Mandalika Main Market in Mataram City is ARIMA (2,0,2). The prediction results show a fluctuating value, with the highest price of cayenne pepper occurring in April. This is because it coincides with Eid al-Fitr.